Covid-19: Implikasi Transportasi Darat dan Logistik di Indonesia - Prasadja Ricardianto (Institut Transportasi dan Logistik Trisakti, 2021)
The purpose of this study is to explain some of the strategic considerations issued by the government for the transportation and logistics sector related to the pandemic situation. Some of the problems in dealing with the Covid-19 pandemic are : (1)There were still significant extension of Covid-19 cases; (2) lack of community discipline in following health protocols; (3) The increase in people's travel from the capital to the regions, even though several transportation operators have imposed some restrictions; and (4) The policies that have been issued by the government related to actions in the field do not yet have an operational design. This research is a literature study from several sources and by comparing several previous pandemic studies. From the findings, it can be concluded that the application of management and protocols for users, such as demand management (reducing crowds, reducing congestion), and the safety and health risks of online motorcycle taxis and safety for all road users is very necessary. Hygienic Logistics is also needed because it is related to the management of the flow of hygienic goods, procurement, material storage and distribution of goods to the point of destination which has an impact on mutually healthy patterns and principles. In the face of this Covid-19 pandemic, the issuance of government regulations, to ensure that people follow the regulations, is very necessary. The public must also follow the WHO health protocol to stop the spread of Covid-19, especially in the transportation and logistics industry.